Biology : a modern introduction - "Beckett, B.S" (Oxford University Press: London, 1997)
Aiming to provide a comprehensive basis for GCSE syllabuses, this book discusses the social, environmental, and technological aspects of biology. It encourages students to explore topics through investigational and experimental work, and features structural drawings, easy-to-copy diagrams, and questions at the end of each chapter.
Keywords: Biology - Textbook